Response to autoimmune enteropathy to cyclosporin A therapy. - Sanderson, I R (1991)
Small bowel enteropathies that are associated with an autoimmune process are often resistant to treatment. Two children with autoimmune enteropathy were treated with cyclosporin A for eight months. Both improved, as assessed by growth, small intestinal mucosal morphology, and carbohydrate absorption. Cyclosporin A is useful in the treatment of autoimmune enteropathy. This report also suggests that T cell activation (which is suppressed by cyclosporin A) is important in the pathogenesis of this condition.